Societal pessimism and trajectories of fertility expectations among Dutch non-parents - Katya Ivanova (Genus)
Abstract This study utilizes prospective data from the Dutch Longitudinal Internet Studies for the Social Sciences (LISS) panel to explore two research questions. First, can distinct trajectories of fertility expectations be identified among Dutch women and men in reproductive age (18 to 45/50) who do not have children? Second, do these trajectories differ in terms of self-reported societal pessimism at the start of that trajectory? We employed joint latent class analysis with Latent GOLD which allowed us to model the trajectories of fertility expectations while accounting for the fact that some of the respondents made the transition to parenthood during observation. The trajectories were estimated from entry into the panel until dropout, the end of the observation period (2022, or until reaching age 45 for women and 50 for men), or until the participant became a parent. For both women (n = 1,260) and men (n = 1,110), three similar classes emerged: 'committed to parenthood' (the largest class), 'uncertain' (24% of women and 22% of men), and 'early commitment to no expectation' (13.3% for women and 9.4% for men). In addition, a fourth class—'later arrivals to expectation of parenthood'—was identified among men. Bias-adjusted comparisons revealed significant differences only among women: those committed to parenthood exhibited the lowest levels of societal pessimism, while the 'uncertain' group reported the highest. These differences persisted even after adjusting for relevant control variables at the time when societal pessimism was captured, including depression levels, income satisfaction, partnership status, and education.